From AChE to BACE1 inhibitors: The role of the amine on the indanone scaffold. Issue 14 (15th July 2015) - Rampa, Angela; Mancini, Francesca; De Simone, Angela; Falchi, Federico; Belluti, Federica; Di Martino, Rita Maria Concetta; Gobbi, Silvia; Andrisano, Vincenza; Tarozzi, Andrea; Bartolini, Manuela; Cavalli, Andrea; Bisi, Alessandra
Graphical abstract: Abstract: In recent years, a progressive increase in age-related disorders could be observed in most western countries, among which Alzheimer's disease (AD) is one of the most challenging. BACE1 could be seen as an attractive target to develop disease-modifying compounds, and in this context, a new series of hybrid molecules was designed and synthesized, based on a previously identified multitarget lead compound. In particular, the amino side chain was appropriately modified to fit BACE1 as additional target. In vitro testing results pointed out compound8 (IC50  = 2.49 ± 0.08 μM), bearing the bulky bis(4-fluorophenyl)methyl)piperazine substituent, as the most potent BACE1 inhibitor of the series.